2018
DOI: 10.1093/pubmed/fdy204
|View full text |Cite
|
Sign up to set email alerts
|

The top six risky behaviors among Iranian university students: a national survey

Abstract: Background Multiple risk-taking behaviors are associated with increased risk of poor educational attainment, morbidity and premature mortality. This study involved a large representative sample of Iranian university students addressing multiple risk behaviors and associated factors. Methods This cross-sectional study included 4261 participants, involving 13 medical universities throughout the country in 2017. The following si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…In this study, the probability of late diagnosis was significantly greater in Iranian men than women. Other studies confirmed that male gender is a major risk factor of risky behaviors such as HIV late diagnosis [ 20 ]. For example, Rice et al, Sun et al and Agaba et al suggested that male gender is significantly associated with a higher risk of late HIV diagnosis [ 21 23 ].…”
Section: Discussionmentioning
confidence: 88%
“…In this study, the probability of late diagnosis was significantly greater in Iranian men than women. Other studies confirmed that male gender is a major risk factor of risky behaviors such as HIV late diagnosis [ 20 ]. For example, Rice et al, Sun et al and Agaba et al suggested that male gender is significantly associated with a higher risk of late HIV diagnosis [ 21 23 ].…”
Section: Discussionmentioning
confidence: 88%
“…22,30,46-48 Risky behaviors exhibited by some students can adversely affect their overall development and well-being as a youth. 49 Evidence shows a negative association between high-risk behaviors and academic achievement and success. This means that students with higher grades are less likely to participate in high-risk behaviors than their classmates with lower grades, and students who do not participate in high-risk behaviors receive higher grades than their classmates who do participate in high-risk behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence rate of such behaviors among Iranian students has also been reported. For example, a study conducted in 2017 among Iranian university students showed that among all 13.5% smoked cigarette, 7.8% drank alcohol, 4.9% had drug abuse and 7.8% had unprotected sex [10].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, in this method of data collection, there is the possibility for the respondents to answer the sensitive questions incorrectly. Considering this issue and keeping in mind the high prevalence rate of high-risk behaviors among Iranian students [10,[21][22][23], we conducted this web-based study to identify the subgroups of students based on risky behaviors, and to determine the prevalence rate of the subgroups among a representative sample of university students in Tabriz, Iran.…”
Section: Introductionmentioning
confidence: 99%